2014
DOI: 10.1155/2014/620682
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cyclosporine Levels on the Development of Acute Graft versus Host Disease after Reduced Intensity Conditioning Allogeneic Stem Cell Transplantation

Abstract: We analyze the impact of cyclosporine (CsA) levels in the development of acute graft-versus-host disease (aGVHD) after reduced intensity conditioning allogeneic hematopoietic transplantation (allo-RIC). We retrospectively evaluated 156 consecutive patients who underwent HLA-identical sibling allo-RIC at our institution. CsA median blood levels in the 1st, 2nd, 3rd and 4th weeks after allo-RIC were 134 (range: 10–444), 219 (54–656), 253 (53–910) and 224 (30–699) ng/mL; 60%, 16%, 11% and 17% of the patients had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…Another great part of the literature proves that a low plasma concentration level of CsA, especially in the early period post-HSCT (i.e., 2-3 weeks post-HSCT) is associated with a much higher risk of aGvHD. 26,[32][33][34][35] To our knowledge, this is the only study providing results that refer to the influence of early cessation of CsA on the occurrence of aGvHD. There is only one reference regarding premature discontinuation of CsA -the research conducted by Cadenas et al 32 Although this study was performed on a completely different population of patients, it contains a brief suggestion that there is no connection between discontinuation of CsA and aGvHD.…”
Section: Discussionmentioning
confidence: 92%
“…Another great part of the literature proves that a low plasma concentration level of CsA, especially in the early period post-HSCT (i.e., 2-3 weeks post-HSCT) is associated with a much higher risk of aGvHD. 26,[32][33][34][35] To our knowledge, this is the only study providing results that refer to the influence of early cessation of CsA on the occurrence of aGvHD. There is only one reference regarding premature discontinuation of CsA -the research conducted by Cadenas et al 32 Although this study was performed on a completely different population of patients, it contains a brief suggestion that there is no connection between discontinuation of CsA and aGvHD.…”
Section: Discussionmentioning
confidence: 92%
“…Recent study authors have reported that high CsA concentrations within three to four weeks after transplantation are more effective in preventing aGVHD. For instance, Garcia et al [18] reported a correlation between CsA concentration and aGVHD in an adult patient with 156 allogenic HSCTs; low…”
Section: Resultsmentioning
confidence: 99%
“…These include use of immunosuppressive drugs singly and in combination [14,15], tailoring the dose of CsA depending on blood levels [16,17] and evaluation of newer immunosuppressive agents in comparison with standard agents [5][6][7][8][9][10]. CsA combined with either MTX or MMF is the most widely used immunosuppressive drug [5,6,8].…”
Section: Discussionmentioning
confidence: 99%
“…Engraftment: Time to myeloid engraftment was defined as first of 3 consecutive days with an absolute neutrophil count of C0.5 9 10 9 /L [17]. Time to platelet engraftment was defined as first of 7 consecutive days when the platelet count is maintained C 20 9 10 9 /L without platelet transfusion.…”
Section: Definitionsmentioning
confidence: 99%